22.3k views
0 votes
To eliminate the y-terms and solve for x in the fewest steps, by which constants should the equations be multiplied by before adding the equations together? First Equation: 5x − 4y = 28 Second equation: 3x - 9y = 30

User KDrewiske
by
4.5k points

2 Answers

1 vote

Answer:

use -9 to multiply the first equation

use -4 to multiply the second equation.

Explanation:

5x-4y=28.....eqn (1)×-9

3x-9y=30....eqn(2)×-4

-45x+36y=-252

-(-12x+36y=-120)

therefore, -33x÷33 =-132÷-33

x=4.

substitute (x=4) in any of the equation. I'm just going to use eqn 1.

5x-4y=28

5(4)-4y=28

20-4y=28

-4y =28-20

-4y÷-4 = 8÷-4

y=-2

so, x=4, y=-2

Note: for proof of answers substitute the answers for x and y and see if you have the same result...e.g

5(4)-4(-2)=28.

User Brucek
by
4.8k points
2 votes

Answer:

The first equation should be multiplied by 9 and the second equation by −4.

Explanation:

User Joarder Kamal
by
5.0k points